Telemonitoring bolnikov z arterijsko hipertenzijo in/ali sladkorno boleznijo tipa 2 v ambulanti družinske medicine - Mihevc, Matic (Medicinski razgledi, 2023)
Backgrounds. Telemonitoring of blood pressure and blood glucose is a promising approach to improve disease outcomes in patients with arterial hypertension and type 2 diabetes. This pilot study aimed to investigate the feasibility and effectiveness of telemonitoring and to gain insight into users’ experiences. Methods. We conducted a pilot pre/post observational study combined with qualitative research methods between December 2018 and December 2019. Sample consisted of 94 patients with arterial hypertension and/or type 2 diabetes on peroral therapy who monitored their blood pressure and blood glucose for three or six months, respectively, and were then followed up to twelve months after inclusion. At baseline, we collected clinical data by questionnaire and drew blood for laboratory analysis. Data were analysed using paired samples t-test. In the qualitative part, we conducted semi-structured telephone interviews with purposively selected patients and healthcare workers (n = 14). Transcripts were analysed using inductive and deductive techniques within the strengths, weaknesses, opportunities, and threats (SWOT) analysis theoretical framework. Results. We found significantly lower systolic blood pressure and glycated haemoglobin values in the three-month telemonitoring group and significantly lower systolic and diastolic blood pressure values in the six-month telemonitoring group compared with baseline. No significant differences were found in the long term. Patients reported overall satisfaction with telemonitoring, but identified the burden of the measurement protocol, the lack of face-to-face contact, and the burden on family members as the main disadvantages. Discussion. Telemonitoring is a feasible and transferable method of care in family medicine practice. Good effectiveness requires careful recruitment of patients, additional staff involvement, and adaptation of measurement protocols to patient expectations.
Keywords: diabetes; hipertenzija; hypertension; mobile health; mobilno zdravje; sladkorna bolezen